A distributed middleware for self–configurable wireless sensor networks. (21st November 2014) - Zhang, Lei; Lim, Alvin; Pan, Yi; Wu, Bin
Heterogeneity, mobility, and resource constraints are the inherent features of the wireless sensor network. In addition, for the wireless sensor network development, the developers have to design the low–level system details adaptive to specific upper layer non–compatible protocols. The distributed services are a middleware, which can make large–scale and resource–constrained wireless sensor network adapt to the dynamic environment in an effective way. It can not only guarantee transmission quality, but also can make application development simple and efficient. In the distributed services, the composition service deals with the dynamics efficiently by managing the nodes to form and maintain task–oriented groups, which not only increases the degree of transparency to the applications, but also improves the reliability and energy efficiency. The entire process releases developers from the tedious low–level work. In this paper, we focus on the demonstration of composition service and its achievement for the self–configurable wireless sensor network.